ChemInform Abstract: Synthesis of New Schiff Bases and Polycyclic Fused Thiopyranothiazoles Containing 4, 6‐Dichloro‐1, 3, 5‐triazine Moiety. Issue 18 (17th April 2014) - Polovkovych, Svyatoslav V.; Karkhut, Andrew I.; Marintsova, Natalia G.; Lesyk, Roman B.; Zimenkovsky, Borys S.; Novikov, Volodymyr P.
Abstract The screening of the in vitro anticancer activity of the synthesized compounds shows that compounds (IVa), (VIIIb), (VIIId) are the most active compounds against different cell lines.